Pathogenicity and transmission dynamics of Gryllus bimaculatus densovirus (GbDV), a significant pathogen in cricket farms in South Korea - Chan-Ouk Kim; Eunsun Kim; June-Sun Yoon; Kibeom Park; Sangmin Ji; Ji-Young Choi; Jeong-Hun Song (Journal of Asia-Pacific Entomology, 2026)

Ferroelectric field gating-assisted thermoelectric energy conversion - Ji Young Park; Sun-Woo Kim; Byoungjin Yoon; Youngbo Shim; Do-Heon Kim; Seong Wook Cho; Jun Chen; Young Hun Jeong; Sangwoo Ryu; Hak Ki Yu; Zhong Lin Wang; Hyesung Park; et al. (Chemical Engineering Journal, 2026)

Rare earth elements as tracers of anthropogenic sources and the influence of land-based aquaculture effluent on trace elements in coastal waters of Jeju Island, Korea - Ijin Lim; Jumi Kim; Wonjin Choi; Jiwoo Kim; Seongha Kim; Seung-Hee Kim; Dong-Hun Lee; Seok Jin Oh; Chulin Sun; Sung-Eun Park; Weol Ae Lim; Taejin Kim (Regional Studies in Marine Science, 2026)

Dual-Drug Stent with Sirolimus and WKYMVm Promotes Endothelialization and Limits Hyperplasia - Yu Jeong Jin; Dae Sung Park; Myung Ho Jeong; Doo Sun Sim; Mi Hyang Na; Chan Woo Kim; Jeong Ha Kim; Hae Jin Kee; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2026)

Environmental factors on microalgal resuspension and dynamics in tidal flats on the west coast of Korea - Hosang Kim; Junghyun Lee; Hun Jun Ha; Sun Min Choi; Yangrae Rho; Jinsoon Park; Ho Kyung Ha; Bong-Oh Kwon; Jong Seong Khim (Marine Pollution Bulletin, 2026)

Evolution and spread of H8Nx avian influenza viruses from wild birds in East Asia, 2019-2024 - Sae-hyeon Park; Sun-Hak Lee; Ye-Ram Seo; Dong-Ju Kim; Young-Jae Si; Hyesung Jeong; Suwoong Lee; Chang-Seon Song; Dong-Hun Lee (Archives of Virology, 2026)

Modulation of tofacitinib pharmacokinetics by isosakuranetin in streptozotocin-induced diabetic rats - Hyeon Gyeom Choi; Sung Hun Bae; So Yeon Park; Hyoungsu Kim; Sun-Young Chang; So Hee Kim (Journal of Pharmaceutical Investigation, 2025)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Lacuna-mimic human-derived nasal septal chondrocyte clusters encapsulated in click chemistry-based hydrogel for in vivo cartilage regeneration - Jung Ho Jeon; Seo Young Cheon; Sun Hwa Park; Hyunji Lee; Seung-Yeon Yoo; Min Young Ahn; Donghyun Lee; Man Soo Kim; Jeong Hun Park; Scott J. Hollister; Heebeom Koo; Sung Won Kim (Chemical Engineering Journal, 2025)

Exposure and health effects follow-up study of residents near a former smelter site - Young-Hun Kim; Da-Som Lee; Jung-Eum Lee; Heon Kim; Yong-Dae Kim; Young-Seoub Hong; Jung-Duck Park; Byung-Sun Choi (Toxicological Research, 2025)

Temporospatial expression of neurogranin in the rat molar development - Jung-Sun Moon; Dong-Wook Yang; Dong-Hoo Kim; Jee-Hae Kang; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2025)

Nanometer-scale tunable mesopores in silica fillers for facile enhancement of epoxy adhesion - Chae Yeon Lee; Min Jeong Kim; Sun Hwan Jeong; Dai-Hwan Kim; Jennifer Kezia Soegijopranoto; Hui Hun Cho; Jun Hyuk Heo; Jung Heon Lee (Chemical Engineering Journal, 2024)

Efficacy and Safety Evaluation of Tacrolimus-Eluting Stent in a Porcine Coronary Artery Model - Dae Sung Park; Mi Hyang Na; Myung Ho Jeong; Doo Sun Sim; Yu Jeong Jin; Hae Jin Kee; Mun Ki Kim; Jeong Ha Kim; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Regulatory role of N-myc downregulated genes in amelogenesis in rats - Dong-Wook Yang; Jee-Hae Kang; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2024)

Urinary metabolite biomarkers of pregnancy complications associated with maternal exposure to particulate matter - Sunwha Park; Minki Shim; Gain Lee; Young-Ah You; Soo Min Kim; Young Min Hur; Hyejin Ko; Mi Hye Park; Sung Hun Na; Young-Han Kim; Geum Joon Cho; Jin-Gon Bae; et al. (Reproductive Toxicology, 2024)

Water-rock interactions of uranium deposits: A field investigation and laboratory batch experiment - Hakyung Cho; Jaeyeon Kim; Seong-Sun Lee; Kang-Kun Lee; Jaeguk Jo; Dongbok Shin; Ji-Hun Ryu; Sung-Wook Jeen (Applied Geochemistry, 2024)

Review of technology and materials for the development of cultured meat - Da Young Lee; Seung Yun Lee; Jae Won Jung; Jae Hyun Kim; Dong Hun Oh; Hyun Woo Kim; Ji Hyeop Kang; Jung Seok Choi; Gap-Don Kim; Seon-Tea Joo; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2023)

Biological characterization of mulberry leaves bioconverted with Viscozyme L - Young Wook Kim; Sun Nyoung Yu; Kwang Youn Kim; Sang Hun Kim; Bo Bae Park; Hyun Cheol Oh; Dong Seob Kim; Kwang Il Park; Soon Cheol Ahn (Molecular & Cellular Toxicology, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Overexpression of the ginseng GH18 gene confers salinity tolerance in Arabidopsis - Gayoung Noh; Ji-Hyun Kim; Sung Won Cho; Young-Hun Kim; Ju-Young Jung; Woo-Jong Hong; Ki-Hong Jung; Gyulim Park; Hong-Joo Son; Ick Hyun Jo; Young Hun Song; Sun Tae Kim; et al. (Plant Biotechnology Reports, 2022)

Identification of novel candidate genes implicated in odontogenic potential in the developing mouse tooth germ using transcriptome analysis - Yeo-Kyeong Shin; Seongmin Cheon; Sung-Duk Kim; Jung-Sun Moon; Jae-Young Kim; Sun-Hun Kim; Chungoo Park; Min-Seok Kim (Genes & Genomics, 2021)

Treadmill Exercise Alleviates Brain Iron Dyshomeostasis Accelerating Neuronal Amyloid-β Production, Neuronal Cell Death, and Cognitive Impairment in Transgenic Mice Model of Alzheimer’s Disease - Dong-Hun Choi; Ki-Chun Kwon; Dong-Joo Hwang; Jung-Hoon Koo; Hyun-Seob Um; Hong-Sun Song; Ji-Sun Kim; Yongchul Jang; Joon-Yong Cho (Molecular Neurobiology, 2021)

Effect of extraction solvent on in vitro anti-inflammatory, antioxidant activity, total phenol and flavonoid contents in Codonopsis lanceolata - Hee-Ock Boo; Jeong-Hun Park; Hag-Hyun Kim; Soo-Jeong Kwon; Sun-Hee Woo (Journal of Crop Science and Biotechnology, 2021)

Bone Generation Following Repeated Administration of Recombinant Bone Morphogenetic Protein 2 - Hye-Ju Son; Mi Nam Lee; Yuri Kim; Hyuck Choi; Byung-Chul Jeong; Sin-Hye Oh; Jung-Woo Kim; Seung-Hee Kwon; Sun-Hun Kim; Soo-Chang Song; Shee Eun Lee; Jeong-Tae Koh (Tissue Engineering and Regenerative Medicine, 2021)

Regulatory role of insulin-like growth factor-binding proteins in odontogenic mineralization in rats - Jung-Sun Moon; Yoo-Sung Nam; Jee-Hae Kang; Dong-Wook Yang; Dae-Yoon Kim; Su-Young Lee; Hyun-Mi Ko; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2021)

The pine wood nematode Bursaphelenchus xylophilus and molecular diagnostic methods - Jin-Pyo Lee; Simranjeet Singh Sekhon; Ji Hun Kim; Sun Chang Kim; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2021)

Dual role of reactive oxygen species in autophagy and apoptosis induced by compound PN in prostate cancer cells - Hyeun Deok Choi; Kwang-Youn Kim; Kwang Il Park; Sang-Hun Kim; Sul-Gi Park; Sun-Nyoung Yu; Young-Woo Kim; Dong Seob Kim; Kyung Tae Chung; Soon-Cheol Ahn (Molecular & Cellular Toxicology, 2021)

Anidulafungin Versus Micafungin in the Treatment of Candidemia in Adult Patients - Jin Woong Suh; Sun Bean Kim; Young Kyung Yoon; Jang Wook Sohn; Min Ja Kim; Jong Hun Kim (Mycopathologia, 2020)

Aptamer-linked immobilized sorbent assay for detecting GMO marker, phosphinothricin acetyltransferase (PAT) - Woo-Ri Shin; Mun-Jong Lee; Simranjeet Singh Sekhon; Ji Hun Kim; Sun Chang Kim; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2020)

Anti-inflammatory effect of bee venom in phthalic anhydride-induced atopic dermatitis animal model - Yu Jin Lee; Myung Jin Oh; Dong Hun Lee; Yong Sun Lee; Jiin Lee; Deok-Hyun Kim; Cheol-Hoon Choi; Min Jong Song; Ho Sueb Song; Jin Tae Hong (Inflammopharmacology, 2020)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Physiological Characteristics and Related Biochemical Parameters of Snow Algae from King George Island, Antarctica - Bo Kyung Kim; HyoungMin Joo; Boyeon Lee; Dong-Hun Lee; In-Young Ahn; Sun-Yong Ha (Ocean Science Journal, 2018)

Cytotoxic Effect on Human Cancer Cells and Antioxidant Activity of Extracts of Codonopsis lanceolata Root using Different Solvent Fractions - Hee Ock Boo; Jeong Hun Park; Hag Hyun Kim; Soo Jeong Kwon; Sun Hee Woo (Journal of Crop Science and Biotechnology, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Evaluation of Physiological Functionalities and Anti-inflammatory Activity on in vitro Cultured Adventitious Root of Platycodon grandiflorum - Hee Ock Boo; Jeong Hun Park; Hag Hyun Kim; Soo Jeong Kwon; Sun Hee Woo (Journal of Crop Science and Biotechnology, 2018)

The use of cefepime as a carbapenem-sparing antibiotic for treating uncomplicated acute pyelonephritis caused by extended-spectrum β-lactamase producing Escherichia coli - Jin Woong Suh; Kyung Sook Yang; Sun Bean Kim; Jong Hun Kim; Jang Wook Sohn; Min Ja Kim; Young Kyung Yoon (Infectious Diseases, 2018)

Stability of Coatings on Sulfide Minerals in Acidic and Low-Temperature Environments - Chan-Ung Kang; Byong-Hun Jeon; Rahul Kumar; Seong-Sook Park; Hyun-Sung Park; Sun-Joon Kim (Mine Water and the Environment, 2017)

A comparative study on generating simulated Landsat NDVI images using data fusion and regression method—the case of the Korean Peninsula - Mi Hee Lee; Soo Bong Lee; Yang Dam Eo; Sun Woong Kim; Jung-Hun Woo; Soo Hee Han (Environmental Monitoring and Assessment, 2017)

Cardiac inotropy, lusitropy, and Ca2+ handling with major metabolic substrates in rat heart - Zai Hao Zhao; Jae Boum Youm; Yue Wang; Jeong Hoon Lee; Jae Hwi Sung; Joon-Chul Kim; Sun Hee Woo; Chae Hun Leem; Sung Joon Kim; Lan Cui; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2016)

Inhibition of pyrite oxidation by surface coating: a long-term field study - Chan-Ung Kang; Byong-Hun Jeon; Seong-Sook Park; Jin-Soo Kang; Kang-Ho Kim; Dong-Kwan Kim; Ui-Kyu Choi; Sun-Joon Kim (Environmental Geochemistry and Health, 2016)

Mitochondria-targeted DsRed2 protein expression during the early stage of bovine somatic cell nuclear transfer embryo development - Hyo-Jin Park; Sung-Hun Min; Hoonsung Choi; Junghyung Park; Sun-Uk Kim; Seunghoon Lee; Sang-Rae Lee; Il-Keun Kong; Kyu-Tae Chang; Deog-Bon Koo; Dong-Seok Lee (In Vitro Cellular & Developmental Biology - Animal, 2016)

Local injection of granulocyte-colony stimulating factor accelerates wound healing in a rat excisional wound model - Guang-Yin Shen; In-Hwa Park; Yi-Sun Song; Hyun-Woo Joo; Yonggu Lee; Jeong-Hun Shin; Kyung-Soo Kim; Hyuck Kim (Tissue Engineering and Regenerative Medicine, 2016)

Behavior, PET and histology in novel regimen of MPTP marmoset model of Parkinson’s disease for long-term stem cell therapy - Jun-Won Yun; Jae-Bum Ahn; Euna Kwon; Jae Hun Ahn; Hyung Woo Park; Hwon Heo; Jin-Sung Park; Hyeonjin Kim; Sun Ha Paek; Byeong-Cheol Kang (Tissue Engineering and Regenerative Medicine, 2016)

Umbilical cord mesenchymal stem cell-conditioned media prevent muscle atrophy by suppressing muscle atrophy-related proteins and ROS generation - Chan-Mi Park; Mi Jin Kim; Sun-Mi Kim; Jin-Ho Park; Z-Hun Kim; Yong-Soo Choi (In Vitro Cellular & Developmental Biology - Animal, 2016)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Generation of high resolution sea surface temperature using multi-satellite data for operational oceanography - Chan-Su Yang; Sun-Hwa Kim; Kazuo Ouchi; Ji-Hun Back (Acta Oceanologica Sinica, 2015)

Prognostic value of hepatoma-derived growth factor-related protein 3 (HRP-3) methylation in non-small cell lung cancer - Young Hun Kim; Won Kee Lee; Jae Yong Park; Dong Sun Kim (Genes & Genomics, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

CoCl2 induces apoptosis through the mitochondria- and death receptor-mediated pathway in the mouse embryonic stem cells - Jin-Ha Lee; Seong-Ho Choi; Min-Woo Baek; Mi-Hwa Kim; Heong-Jun Kim; Sun-Hun Kim; Sang-Jin Oh; Hong-Ju Park; Won-Jae Kim; Ji-Yeon Jung (Molecular and Cellular Biochemistry, 2013)

Carpesium abrotanoides extract inhibits cyclooxygenase-2 expression induced by toll-like receptor agonists - Do-Won Jeong; Eun-Kyeong Lee; Chung-Ho Lee; Se Jin Lim; Gyo-Jeong Gu; Ji Hun Paek; Songmun Kim; Soon Sung Lim; Hyung-Sun Youn (Toxicology and Environmental Health Sciences, 2013)

Regulation of bone formation using rapamycin-induced BMP2 expression system: influence of implanted cell number - Dong-Jin Lim; Bae Keun Park; Won Gu Jang; Kkot-Nim Lee; Renny Franceschi; Sun-Hun Kim; Shee-Eun Lee; Jeong-Tae Koh (Molecular & Cellular Toxicology, 2010)

1,3-Dichloro-2-propanol induces apoptosis via both calcium and ROS in mouse melanoma cells - Sun Young Park; Young Hun Kim; Young Hee Kim; Sang-Joon Lee (Biotechnology Letters, 2010)

Molecular epizootiology of infectious bursal disease (IBD) in Korea - Woo-Jin Jeon; Kang-Seuk Choi; Dong-Woo Lee; Eun-Kyoung Lee; Sang-Ho Cha; Sun-Hee Cho; Jun-Hun Kwon; Yeo-sung Yoon; Sun-Joong Kim; Jae-Hong Kim; Hyuk-Joon Kwon (Virus Genes, 2009)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Improving the yield of soluble 6xHis-tagged interferon-α via the addition of repressor of the araBAD promoter system in Escherichia coli - Kyung-Hwan Jung; Young-Seo Park; Ji-Hyeon Yeon; Sung-Hun Kim; Sun Kyun Yoo; Byeong-Churl Jang (Biotechnology Letters, 2008)

Buprederm™, a New Transdermal Delivery System of Buprenorphine: Pharmacokinetic, Efficacy and Skin Irritancy Studies - In Park; Dongwon Kim; Jindeog Song; Chang Hoon In; Seung-Wei Jeong; Sang Hun Lee; Bumchan Min; Dongho Lee; Sun-Ok Kim (Pharmaceutical Research, 2008)

Geochemistry and tectonic implications of Proterozoic amphibolites in the northeastern part of the Yeongnam massif, South Korea - Yoji Arakawa; Kye‐Hun Park; Nam‐Hoon Kim; Yong‐Sun Song; Hiroshi Amakawa (Island Arc, 2003)
Amphibolites in the Haenggongni area (Haenggongni amphibolite) and the Okbang area (Okbang amphibolite) in northeastern Yeongnam massif, South Korea occur as a sill‐like body or inclusions within the metasedimentary sequences of the Proterozoic Wonnam Group. Major and trace element characteristics demonstrate that both amphibolites have tholeiitic chemical affinity. They are characterized by nearly flat rare earth element (REE) patterns, and low contents of immobile incompatible elements and have low values of Zr/Y, Ti/Y, La/Nb and Ta/Yb ratios, indicating enriched (E)‐type mid‐oceanic ridge basalt (MORB) affinities for their protoliths. This suggests that amphibolite protoliths formed in an extensional rift setting leading up to ocean opening. In combination with the previous studies in Yeongnam massif, three protolith types of amphibolites are assumed (E‐type MORB, within‐plate basalt and volcanic arc basalt). They could have been originated in different tectonic settings and/or different episodes. These characteristics are clearly different from the amphibolites in the Gyeonggi massif and Okcheon belt, in which most of the amphibolites show a within‐plate basalt affinity that developed in continental rift zone.

Stereochemical control in diastereoselective reduction of α-substituted-β-ketoesters using a reductase purified from Kluyveromyces marxianus - Joo Hwan Cha; Ae Nim Pae; Kyung Il Choi; Yong Seo Cho; Wook Hyun Kim; Ye Sun Han; Hong-Chul Yun; Jongsoo Lee; Hun Yeong Koh; Eun Lee (Biotechnology Letters, 2002)